Neurological manifestations in dogs with acute leukemia - Lyseight, Filipa L. S.; Pittaway, Charles; Dennis, Ruth; Cherubini, Giunio B. (Frontiers in Veterinary Science, 2024)
Canine acute leukemia is a rare hematopoietic neoplasm. Neurological abnormalities have been frequently reported in dogs with acute leukemia (AL). However, the description of the presentation and findings are limited. This study aimed to describe the clinical findings in dogs with acute leukemia presenting with neurological signs as their primary complaint. The database of a private referral hospital was searched for cases that presented to the neurological department with neurological deficits and were subsequently diagnosed with acute leukemia. Six cases were included; all had neurological clinical signs and an abnormal neurological examination. All cases had a focal neuroanatomical localisation on neurological examination (brain n = 4; spinal = 2). Out of the four dogs with a complete magnetic resonance imaging (MRI) study, there was an ill-defined infiltrative pattern with abnormal signal intensity in the central nervous system (CNS) in three dogs and the loss of grey and white matter differentiation in the brain (n = 2) and/or spinal cord (n = 2). Other MRI findings included abnormal meningeal enhancement (n = 3), changes affecting spinal nerves and epaxial muscles (n = 2), and lymphadenopathy in the field of view (n = 2). The bone marrow assessment on MRI showed evidence of signal change (n = 3), characterized by a loss of normal fat opacity and an abnormal degree of contrast enhancement. The cerebrospinal fluid (CSF) analysis of the four dogs showed an increased protein level with non-specific pleocytosis and without evidence of malignant cells. Treatment with cytotoxic medication was implemented in two dogs. The dogs diagnosed with acute leukemia had focal neuroanatomical localisation, an infiltrative CNS pattern, and bone marrow remodulation on MRI with an increase in CSF protein and negative cytology analysis.